Prediction of acute lymphoid leukemia using Privacy Preserving Neural Network - Khilji, Ishfaque Qamar; Saha, Kamonashish; Shonon, Jushan Amin; Israq, Ragib (BRAC University, 2021)
Cataloged from PDF version of thesis.